CỐ ĐỊNH KHÁNG THỂ IgM KHÁNG VI RÚT BẰNG PHƯƠNG PHÁP CỘNG HÓA TRỊ CHO CẢM BIẾN MIỄN DỊCH ĐIỆN HÓA - Huy, Trần Quang; Hồng Hạnh, Nguyễn Thị; Chung, Phạm Văn; Ngà, Phan Thị; Tuấn, Mai Anh (Vietnam Journal of Chemistry, 2012)
In this study, we describe the immobilization methods of IgM antibody against Japanese Encephalitis (JE) virus for electrochemical immunosensors. These methods were experimented in order to optimize the efficiency, orientation of antibody as well as minimize the loss of its activity on the sensor surface over the time. Atomic force microscope, Fourier transform infrared spectrometer and fluorescence microscope were performed to survey the characterizations of the sensor surface after using different immobilizing methods of the antibody. The results showed that the silanized sensors using 5% glutaraldehyde as a cross linker between IgM antibody and 3-aminopropyl-triethoxy-silance (APTES) layer is the most advantageous method for electrochemical immunosensors application, it revealved that the signal detection is 2 to 3 fold higher than the the use of other methods. The detection of immunosensors was sensitive, with the quick response time, about 5 minutes and stability after 20 minutes for the detection of JE viral antigens in the sample diluted 60 times in comparison with the initial dilution used for MAC-ELISA tests. Keywords: Covalent immobilization, IgM antibody, IEV antigens, immunosensor, biosensor.